Analysis of Paranet Techniques in Fulfilling National Food Diversification as a Solution to the Highland Water Crisis - Aldi Adi Pratama; Faathir Alfath Risdarmawan (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2023)
The need for food in the industrial world tends to increase every time, this is due to Indonesia's population growth rate continues to increase. This prospect is said to be positive, because it also absorbs the level of sales of local agricultural commodities, so that the level of welfare also increases. UKM XYZ is a social enterprise that was formed together, with the aim of collecting various harvests carried out by farmers, which are then processed into processed food products, so as to increase the cost of added value income. The technique in this activity is carried out manually, with the form of nets used that must cover the plantation area as a whole, without gaps, so that the irrigation process using dew can be carried out perfectly. The results of the water quantity value from the paranet net technique are greater than the quantity value. rain of hope. This makes it an alternative technique that can be adopted by farmers in dealing with climate change or prolonged climate crises such as drought. The results of the production value of the production quantity of the harvest value deposited to SMEs XYZ in the three month period (January – March 2023), show a better increase than the initial data period (October – December 2022). The high water quantity value from the paranet netting technique must be adjusted to the conditions of the slopes or the steepness of agricultural land, so that it does not pose a risk of landslides or excessive abrasion, which is detrimental to farmers